Dynamic bending responses of CFRP thin-walled square beams filled with aluminum honeycomb. (November 2018) - Xiao, Yong; Hu, Yefa; Zhang, Jinguang; Song, Chunsheng; Liu, Zhaobing; Yu, Jingui
Abstract: Aluminum honeycomb-filled Carbon Fibre Reinforced Plastic (CFRP) thin-walled square beams is a new outstanding energy absorption component. In this paper, dynamic impact tests for bending of aluminum honeycomb-filled CFRP beams with different configurations are carried out, and the failure mode and force responses are investigated. For the failure mode, modified Chang-Chang failure criteria are used to predict tensile and compressive fibre failure, as well as tensile and compressive matrix failure. Numerical simulation of the tests is also performed, and the accuracy is validated by the experimental results. The influences of some factors, including the wall thickness, fibre direction, stacking sequence, and impact velocity, on the bending resistance, are analyzed. The effect of aluminum honeycomb filler on the crashworthiness characteristics is also discussed. The results show that the energy absorption and specific energy absorption of filled composite tubes can significantly increase by 104.3% and 26.8% respectively compared with those of CFRP hollow beams. This study demonstrates the potential of CFRP beams filled with aluminum honeycomb to be used as energy absorbers. Highlights: Dynamic three-point bending tests are performed for aluminum honeycomb-filled CFRP beams. The typical load-displacement curves are studied to evaluate crashworthiness. Modified Chang-Chang failure criteria are used to predict fibre failure and matrix failure. The influences of some factors on crashworthiness of aluminum honeycomb-filled CFRP beams are investigated. Aluminum honeycomb filler in performance improvement of CFRP hollow beams.